Fenomena pendidikan elitis dalam sekolah/madrasah unggulan berstandar internasional (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2012)
This article aims to review and discuss the phenomenon of eminent school/ madrasah in international standard in Indonesia that has a tendency to be elitist and reproductive force is not productive force. There are two formulations of problem studied in this article, namely how the elitism emerges in the eminent school / madrasah in international standard? Then, how to recommend the eminent school / madrasah in order to ensure equitable access of education for all children throughout the community of nations,especially among the poor? Artikel ini bertujuan untuk mengkaji dan mendiskusikan fenomena sekolah/ madrasah unggulan berstandar internasional di Indonesia yang memiliki kecenderungan elitis dan menjadi reproductive force bukan productive force. Ada dua rumusan masalah yang dikaji dalam artikel ini, yaitu bagaimana elitisme itu muncul dalam sekolah/madrasah unggulan berstandar internasional? Kemudian,bagaimana cara merekonstruksi sekolah/madrasah unggulan tersebut agar dapat menjamin akses pendidikan yang berkeadilan bagi semua anak bangsa dari seluruh kalangan masyarakat, terutama kalangan rakyat miskin?